Penyelewengan Kewenangan dan Kegagalan Pengawasan Pemerintahan: (Studi Kasus Korupsi Proyek SPAM Kementerian PUPR) - M. Haidar Hafizh Daniar; Muhammad Fathoni Ridzakiy; Mohamad Davit Triandi Priatna; Ivan Darmawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This article analyzes the mega-corruption case of the Drinking Water Supply System (SPAM) project at the Directorate General of Human Settlements, Ministry of Public Works and Housing (PUPR), Fiscal Year 2017–2018, from the perspective of government oversight. The Corruption Eradication Commission (KPK) sting operation in December 2018 revealed a systemic corruption network involving ministry officials, private contractors, and BPK members. This study aims to identify the failure of layered oversight, including Internal Control (WASKAT), functional supervision by the Inspectorate General, and external oversight by BPK, which allowed bid-rigging, a 10% commitment fee collection, and audit manipulation to occur for years. Using the public administration oversight theories of George R. Terry, Robert J. Mockler, Paulus Effendi Lotulung, and WASKAT, the study finds that oversight dysfunction resulted not from the absence of regulations but from weak managerial leadership implementation and bureaucratic culture influenced by ewuh pakewuh and negative corps solidarity. BPK members' involvement in manipulating audit findings and tender winners indicates state capture practices that undermine accountability. Restoring oversight integrity requires AI-based audit digitalization in LPSE, hierarchical accountability, procurement officer rotation, and stronger BPK independence through blockchain-based audit documentation.